Rekayasa Genetik pada Nyamuk Penyebab Malaria: Kajian Literatur - Romadhona, Harisma Atiqur; Qushayyi, Muhammad Faiq; Sari, Rahmawati Yanita; rohmah, sayyidah auliyar (STKIP HARAPAN BIMA, 2024)
Indonesia is a country with a heterogeneous tropical climate and is also vulnerable to the impacts of regional and global climate change. Malaria is transmitted by the Anopheles sp mosquito, the clinical and pathological symptoms of malaria are almost exclusively caused by the asexual phase of plasmodium in erythrocytes. This research uses a qualitative descriptive approach, because the data used comes from descriptions of words, with the type of library research or literature review. Library research and library searches are not only carried out as initial steps in preparing a research framework but also serve as library sources that are used as sources of research data. Search for data via Google Scholar using the keywords